Stage-resolved transcriptomic profiling of Anastrepha ludens (Diptera: Tephritidae) from egg to adult: molecular signatures of a notorious polyphagous fruit-fly pest - Cerqueda-García, Daniel; Osorio-Paz, Ixchel; Carpinteyro-Ponce, Javier; Ibarra-Laclette, Enrique; Altúzar-Molina, Alma; Aluja, Martín (Frontiers in Insect Science, 2025)
This study explores the transcriptional dynamics of the polyphagous Mexican Fruit Fly, Anastrepha ludens, across five developmental stages, revealing distinct gene expression patterns unique to each stage. We identified 9,762 DEGs associated with the four developmental stages. During the egg stage, we identified the greatest number of differentially expressed genes exhibiting a pronounced activity of metabolic pathways, particularly the Mitogen-Associated Protein Kinase (MAPK) signaling pathway, which is essential for embryonic development and defense mechanisms. The second larval instar stage mainly focused on growth, as shown by the overexpression of the Transforming Growth Factor Beta (TGF-beta) pathway. In the third larval stage, genes are significantly enriched in cuticle structure and transmembrane transport. In the pupal stage, the importance of the TGF-beta and mTOR pathways emerged, vital for tissue homeostasis and development. The adult stage exhibited sustained expression of the FOXO pathway, enhancing stress resistance crucial for survival and reproduction. Additionally, we noted differences in odor-binding protein (OBP) expression between sexes, hinting at their potential role in mating behavior. These findings provide fundamental information about the life stages of A. ludens, highlighting the importance of specific signaling pathways and OBPs, which could help improve mass rearing processes and management strategies for this notorious tephritid pest.